Quy trình kỹ thuật cơ giới hoá gieo sạ tăng hiệu quả và giảm phát thải khí nhà kính trong sản xuất lúa ở đồng bằng sông Cửu Long - Department of Crop Production, Vietnam (Department of Crop Production, 2023)
The national technical guideline on mechanized wet direct-seeding for increased productivity, quality, and reduced carbon footprint in rice production in the Mekong River Delta (MRD) was issued on 31 October 2023 by Department of Crop Production, MARD of Viet Nam. This provides the guidance on advanced direct seeding and associated technlogies, such as land preparation, seed preparation, mechanized wet direct-seeding options, and crop care recommendations. This technical guideline is for rice production in MRD and other regions; in particular, in the areas for high-quality and low emission rice production.